STUDI FARMAKOFOR RESEPTOR ESTROGEN α SEBAGAI TARGET TERAPI KANKER SERVIKS - Nursalam Hamzah; Ahmad Najib; Fatmawati S (Universitas Islam Negeri Alauddin Makassar, 2014)
One of the target on chemotherapeutic agent especially for curing cervical cancer is the inhibition of estrogen activity on estrogen alpha receptors. Estrogen stimulates human papilloma virus oncogene expression, promotes cervical cancer (CC) cell proliferation and prevents apoptosis. Therefore, blockage of estrogen function may have therapeutic application to CC. SERMs (Selective Estrogen Receptor Modulator) are the group of subtances which inhibit the activity of estrogen on its receptor. The aim of this reserach is to determine the features that are important pharmacophore on anti-cercix cancer activity of compounds on ER-α receptor that depended on this receptor. Modeling and determination pharmacophore features created using the program MOE application version 2009. Screening Virtual of chemical compounds to look for natural ingredients in accordance with pharmacophore features that have been made, performed using MOE. The result of the pharmacophore showed that 4-hydroxitamoxifen and its analogues have an antagonism activity on estrogen alpha receptor.